Magnetic entropy dynamics in ultrafast demagnetization. (16th October 2020) - Goharshenasanesfahani, S; Smadici, S
Abstract: A double polarization and temperature modulation configuration was applied to measure the magnetization and magnetic entropy dynamics in ultrafast demagnetization. Two magnetic properties, obtained by subtracting measurements made at opposite fields, have the same onset at small delays and different relaxations at large delays. The different dynamics suggests that spin relaxation in ultrafast demagnetization is a combination of two processes.